PENGARUH FILM ANIMASI NUSSA DAN RARA DALAM MENINGKATKAN MINAT BELAJAR AQIDAH AKHLAK SECARA DARING - Malik, Zenda Abdul (Tarbawi : Jurnal Pendidikan Islam, 2023)
The article discussed the effects of the Nussa Animation Film and Rara in increasing aqidah edifying interest online. The method used isa qualitative type of study by collecting data of related journals or articles based on factors that support the object, then analyzing the factors for its role and then synthesizing it to make it newer. This article discusses the influence of the nub animation film and rara in improving children's learning especially akidah moral subjects online. Where a few layers from the world's vast economic divide come from, one of which is a technological development. Technological developments make it easier for a parent to give learning to his or her children. But sometimes the lack of control of parents makes children a bet, for that parent should be the first place of education for children. Based on the question, the purpose of this research could tell how far islamic moral messages have affected both the nussa and rara animation films and make it easier for parents to provide effective and non-boring learning by providing a viewing of nussa animation and rara's many moral roles for children's lives.